2010
DOI: 10.1007/s00268-010-0727-6
|View full text |Cite
|
Sign up to set email alerts
|

Marjolin’s Ulcers in sub‐Saharan Africa

Abstract: Marjolin's ulcers in sub-Saharan African have a shorter latent period, and they occur in younger patients. Provision of early stable wound cover is essential for prevention of malignant degeneration of scars, while early appropriate intervention is crucial in the treatment of chronic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
22
2
Order By: Relevance
“…Current studies in Africa have reported that the mean age of patients with Marjolin's ulcers is lowering and appears to be affecting younger patients over the years [12,20]. It also appears that the transition time is getting shorter [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies in Africa have reported that the mean age of patients with Marjolin's ulcers is lowering and appears to be affecting younger patients over the years [12,20]. It also appears that the transition time is getting shorter [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from western countries have shown that the average age at diagnosis is in the fifth decade of life with a range of 18-84 years, and men are three times more frequently affected than women [11]. In Sub-Saharan Africa, Marjolin's ulcer appears to be affecting younger patients and the transition time is getting shorter over the years [12]. …”
Section: Introductionmentioning
confidence: 99%
“…supposed to be inversely proportional to the age of onset of predisposing condition. 9 Shortest lag period ranged from 4 weeks 10 to 70 years, 6 mean time being 36 years after sustaining burns.…”
Section: Discussionmentioning
confidence: 99%
“…5 Majority of cases reported are squamous cell carcinoma, 6 over the extremities, 7 commonest region of body involved are lower limbs 40%, 30% for head & neck regions, 20% for extremities & 10% for trunk. 7 Though various unifactorial theories like Virchow's theory of chronic irritation, 12 Friedwald and Rouse cocarcinogenic theory, 13 Treves and Pack's 1 toxin theory, Ribet's theory of epithelial implantation 9 etc. have been proposed for the pathogenesis of development of malignancy in scar patients, multifactorial theory have been propounded for malignant transformation, which proposes the combination of above theories as pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, although the duration of the Danish study was 25 years, 13 it is possible that this period was insufficient to cover the full latent period between exposure (time of burn injury) and disease (skin cancer development) in patients with burn scars, because clinical studies have reported mean latent periods ranging from 23 to 48 years. [16][17][18][19] The two population-based studies identified in this systematic review were well-defined cohorts accrued through national hospital inpatient registration. Because cancer registration is mandatory and almost 100% for all cancers in Denmark and Sweden, including keratinocytic skin cancers, it is likely that case ascertainment was close to complete, particularly for skin cancers occurring at the site of a previous burn injury.…”
Section: Discussionmentioning
confidence: 99%